PROMOSI WISATA CUKANG TANEUH OLEH KELOMPOK SADAR WISATA DI KECAMATAN CIJULANG KABUPATEN PANGANDARAN - Rizky Firmansyah Tajudin; Asep Nurwanda; Dini Yuliani (JOURNAL SAINS STUDENT RESEARCH, 2025)
Tourism promotion using promotional tools in promotional techniques in tourism carried out by the Tourism Awareness Group in Cijulang District, Pangandaran Regency. This promotion helps tourism awareness groups to report product results to consumers, provide all forms of promotion materials planned to be given to the public and as a company spokesperson with other parties who need information about everything about Cukang Taneuh tourism more clearly so that it can increase tourist visits more optimally.